Possibilities of Complex Ultrasound Examination in the Assessment of Hemodynamic and Structural Features of Retinal Capillary Hemangioma - V. V. Neroev; T. N. Kiseleva; P. A. Ilyukhin; K. A. Ramazanova; M. A. Ryabina; A. Y. Novikova (Oftalʹmologiâ)
Purpose: to study the possibilities of complex ultrasound examination in the assessment of hemodynamic and structural features of retinal capillary hemangioma (RCH).Patients and methods. 26 patients (35 eyes) with RCHs at the age of 11 to 53 years (mean 26.6 ± 9.4 years) were examined. Ultrasound examination was performed using B–mode image, echodensitometry, Color Doppler Imaging (CDI) and pulsed Doppler (PD). The peak systolic velocity (Vsyst), the end-diastolic velocity (Vdiast) of the blood flow, and the resistance index (RI) in the orbital vessels were examined using CDI and PD. Qualitative and quantitative assessment of blood flow in a feeding artery and a draining vein of the RCHs were performed. The follow-up efficiency evaluation of the laser coagulation of RCH was performed in 12 eyes. Results. The elevation of RCH was 1.7 ± 0.7 mm (from 0.5 to 3.3 mm) on average, the base diameter — 5.4 ± 2.1 mm (from 1.8 to 11.5 mm). The acoustic density varied from 42 to 176 (mean 109.6 ± 30.9) in relative units. The indices of Vsyst were from 5.5 to 21.4 cm/s (mean value — 10.6 ± 4.2 cm/s) in the feeding arteries, from 3.06 to 14.3 cm/s — in veins (mean value — 4.9 ± 2.4 cm/s). A significant increase in the blood flow velocity in the central retinal vein (CRV), a decrease in RI in the central retinal artery (CRA) and short posterior ciliary arteries (SPCAs) were determined. In 3 (8.6 %) eyes, in the absence of echographic manifestations of small RCHs of optic nerve head (ONH), there was an increase of the blood flow velocity in the CRV (the mean value was 8.95 ± 1.15 cm/s). After treatment, B-scan ultrasonogram showed no visualization of RCHs in 3 eyes. A significant decrease (31 %) of prominence compared to the baseline values was registered in 9 eyes (66.7 %). A decrease of the tumor base the diameter by an average of 37.7 % was also registered in 7 eyes (58.3 %). A significant decrease (26.3 %) in Vsyst in arterial-type feeding vessels was determined. Conclusion. Significant changes in regional ocular blood flow in RCH were registered. The increase of blood flow in the CRV at the localization of RCH on the ONH can be an additional differential diagnostic criterion of the disease. The hemodynamic instability in the retinal vessels feeding the RCH and the positive dynamics of the blood flow after laser coagulation were determined.